INFLUENT TEMPERATURE EFFECTS ON THE ACTIVATED SLUDGE PROCESS AT A MUNICIPAL WASTEATER TREATMENT PLANT - Marius-Adrian BREHAR; Melinda VÁRHELYI; Vasile-Mircea CRISTEA; Daniel CRÎSTIU; Paul-Şerban AGACHI (Studia Universitatis Babeș-Bolyai. Chemia, 2019)
The influent temperature has an important effect on the activated sludge process at the municipal Wastewater Treatment Plants (WWTPs). This research is associated to a case study of a Romanian municipal WWTP with Anaerobic-Anoxic-Aerobic (A2O) layout. Based on mathematical modelling, the influent wastewater temperature effect on the effluent components concentration and on the concentration of pollutants and biomass concentrations at the outlet of biodegradation basins aerobic zone was studied. Three influent temperature profiles were considered and implemented in the simulator. They reveal the representative 22 days period of the months: February (coldest water season), May (intermediate season) and July (warmest season). The simulations were performed both in steady and dynamic state. It was observed that higher influent temperatures intensify the nitrification and denitrification processes. As a result, the concentration of the nitrogen compounds in the effluent and at the end of the bioreactors decreases with the increase of the temperature. The carbon rich organic components feature a minor increase in the effluent. The study reveals that short time daily influent temperature changes do not have significant effect on the effluent components concentration, but the long-term ones affect the WWTP performance.